The role of arginine as nitrogen doping and carbon source for enhanced oxygen reduction reaction. (18th January 2018) - Kim, Do-Hyoung; Kwak, Da-Hee; Han, Sang-Beom; Park, Hyun-Suk; Park, Jin-Young; Won, Ji-Eun; Ma, Kyeng-Bae; Yun, Seok-Hyeon; Kwon, Suk-Hui; Koh, Moon Hyun; Park, Kyung-Won
Abstract: Doped carbon nanostructures as non-precious metal (NPM) catalysts for oxygen reduction reaction (ORR) in acid medium are mainly synthesized using 5, 10, 15, 20-tetrakis (4-methoxyphenyl)-porphyrin-Fe (III) chloride (Fe-TMPP) as doping and carbon sources. In this study, the doped carbon nanostructures used as cathode NPM catalysts for ORR are prepared using a mixture of iron phthalocyanine (FePc) and arginine as doping and carbon sources. The morphology and composition of the as-prepared samples are characterized using field-emission scanning electron microscopy, field-emission transmission electron microscopy, and energy dispersive X-ray (EDX) spectroscopy. The crystal and pore structures are analyzed using X-ray diffraction method, Raman spectroscopy, and nitrogen adsorption/desorption method. The sample prepared using a precursor mixture with a proper ratio of FePc and arginine exhibits significantly superior ORR performance, i.e. high specific activity, enhanced half-wave potential, and improved stability in an acid medium, as even compared to a commercial Pt/C. The improved ORR properties is mainly attributed to high portion of pyridinic N state with a relatively high specific surface area, which can result from the FePc precursor surrounded by the fused arginine. Graphical abstract: Highlights: Doped carbon nanostructures were prepared using iron phthalocyanine and arginine. The doped carbon nanostructures showed superior ORR performance. The improved ORR performance is attributed to high portion of pyridinic N state. The structure favorable for ORR can result from the FePc surrounded by the arginine.